2009
DOI: 10.1016/j.jhealeco.2009.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term labour-market performance of whiplash claimants

Abstract: Abstract:A whiplash is a sudden acceleration-deceleration of the neck and head, typically associated with a rear-end car collision that may produce injuries in the soft tissue. Often there are no objective signs or symptoms of injury, and diagnosing lasting whiplash associated disorders (WAD) is difficult, in particular for individuals with mild or moderate injuries. This leaves a scope for compensation-seeking behaviour. The medical literature disagrees on the importance of this explanation. In this paper we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 27 publications
(27 reference statements)
1
40
0
Order By: Relevance
“…2 In recent studies, up to 50% of WAD patients 3,4 and 30% to 100% of postsurgical CR patients 4-9 report personal suffering from prolonged symptoms, with persistent pain, disability, and reduced health-related quality of life (HRQoL). Physical function and treatment have been severely understudied both for CR patients scheduled for surgery 9,10 and for chronic WAD patients, 11 particularly for patients with verified neurological and musculoskeletal findings (WAD Grade III).…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent studies, up to 50% of WAD patients 3,4 and 30% to 100% of postsurgical CR patients 4-9 report personal suffering from prolonged symptoms, with persistent pain, disability, and reduced health-related quality of life (HRQoL). Physical function and treatment have been severely understudied both for CR patients scheduled for surgery 9,10 and for chronic WAD patients, 11 particularly for patients with verified neurological and musculoskeletal findings (WAD Grade III).…”
Section: Introductionmentioning
confidence: 99%
“…There are also significant costs on a personal level for a large proportion of the injured, LethPetersen et al found that only half of whiplash claimants returned to the same earning level that they had prior to the injury [37]. The mean cost for productivity loss per person found in this study (10,400 Euros) can be compared with a study from Sweden showing that whiplash injuries give rise to an approximate eight days average increase in the number of sick days from the year prior to the whiplash injury to the year after the injury [17].…”
Section: Discussionmentioning
confidence: 99%
“…It gives a broad effect on both society and for the individual in terms of suffering, health, productivity, and costs (1). About 50% of those who suffer a whiplash trauma continue to report neck pain one year after their injury (4), and among those with persistent symptoms about 50% experience persistent reductions in earnings relative to the trauma (5). Yet there is no clear evidence for any effective treatments for either acute, subacute or chronic Whiplash Associated Disorders (WAD), mainly due to lack of high quality studies (6,7).…”
Section: Background Whiplash Associated Disorders (Wad)mentioning
confidence: 99%
“…Although it is commonly believed that claiming compensation leads to worse recovery, the opposite, that poor recovery may lead to compensation claims, is just as possible (21). Longitudinal data on neck pain up to 24 months post injury show that removing the financial incentive to over-report symptoms has no effect on self-reported neck pain in WAD (22), and compensation-seeking behaviour is not the main explanation for this group (5). Furthermore, there is a growing body of evidence of objective findings in people with WAD (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Insurers Motor and Liability Department Claims That "The Fmentioning
confidence: 99%